Testicular Injection of Autologous Platelet-Rich Plasma (PRP) to Enhance the Sperm Parameters in Rabbit - Alaa Kamil Abdulla; iD, Tarek Rebai; Dhia Hussein Jassim AlDelemi (Genius Journals, 2022)
This study aims to determine the perfect time for semen collection after intra-testicular platelet-rich plasma to get good and improved semen. Twenty male New Zealand rabbits were used, about 10 to 12 months aged, which randomly divided into two equal groups; the control group and the PRP group which was enriched with 200 μl (4000 × 109 platelets/1 µl) single-dose by intra-testicular injection. The Laboratory analysis of all animals continued at four-time points (4thwk, 6thwk, 8thwk and 10thwk) by measuring the concentration of the Testosterone, Vascular Endothelial Growth Factor (VEGF) and Insulin-like Growth Factor-1 (IGF-1) in the seminal plasma by ELISA technique. Furthermore, the semen analyses which applied by the Computer Assisted Sperm Analysis (CASA) device.
Keywords: Platelet-rich plasma; Rabbit; Sperm Parameters; Testis Function